State Policy in the Field of Waste Management: Effective Global Practices for Russia - O. V. Kudryavtseva; S. V. Vasiliev (Мир новой экономики)
Globally, there are a number of successful practices and initiatives aimed at solving the problem of waste management and reducing its negative impact on the environment. The relevance of their application is due to the growing volume of waste accumulation, which is becoming a global environmental problem.The aim of the article is to identify possible economic benefits based on the analysis of the possibilities of applying global practices in the field of waste management in Russia.Research methods: economic and statistical analysis, comparison, generalization, synthesis, systematic approach.The results of the study. The article presents results of potential implementation of the “waste-free city” concept. Possible economic benefits have been identified when incinerators are put into operation in some regions, electricity is generated by incineration of waste sent to landfills, and traditional fuel is saved in the production of “green energy” at these plants. The benefits of using the reverse logistics mechanism have been determined. The introduction of reverse logistics practices encourages the solution of waste reduction tasks, sustainable competitiveness, and economic benefits. The results of effective deposit repayment programs implemented in many countries are summarized.Scientific novelty. Based on the results of the analysis, the authors substantiate the application of world practice in Russia.Practical significance: the research results can be applied to develop project activities, development strategies, and to adapt global practices to Russian realities, taking into account economic and environmental consequences, while choosing the most appropriate mechanisms to support effective waste management practices.